2002
DOI: 10.1093/geronb/57.3.p195
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving as a Dyadic Process: Perspectives From Caregiver and Receiver

Abstract: Most family caregiving research has relied on the perspective of the caregiver but has not systematically examined the views and opinions of the elder who is receiving care. The present study examined 63 caregiving dyads to determine how the responses of each member had an impact on the well-being of the other member of the dyad. Caregiver relationship strain predicted his or her own depression and negative health, but no significant association was found between caregiver and care recipient outcomes. Multilev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
218
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(231 citation statements)
references
References 58 publications
6
218
0
7
Order By: Relevance
“…The use of multilevel modeling to control for the interdependent nature of dyadic data has been well-described elsewhere (Lyons et al, 2002). In brief, our approach accounted for measurement error and interdependence of data at the item level, and results in empirical Bayes Table 1 Patient and caregiver determinants of dyadic contributions to heart failure self-care.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multilevel modeling to control for the interdependent nature of dyadic data has been well-described elsewhere (Lyons et al, 2002). In brief, our approach accounted for measurement error and interdependence of data at the item level, and results in empirical Bayes Table 1 Patient and caregiver determinants of dyadic contributions to heart failure self-care.…”
Section: Discussionmentioning
confidence: 99%
“…43 However, the estimates presented here are likely conservative because care recipients usually understate impairment or disability compared with assessments by caregivers. [80][81][82] Furthermore, the self-reported data used in this analysis have also been previously used to estimate informal costs of caregiving for patients with heart failure, stroke, dementia, depression, and diabetes mellitus. 18,19,33,35,83 We did not examine the spillover effects on caregivers; it is well documented that prolonged and intense caregiving effort exerts a devastating toll on caregiver health manifested as burden, depression, reduced quality of life, and increased risk for CVD events and other chronic conditions 14,15 compared with noncaregivers of the same age.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…In this study, caregivers found it burdensome that the care recipient is often unaware of the burden that the provision of care entails. Although incongruence in the mutual appraisal of caregiving difficulties has been reported (Lyons, Zarit, Sayer & Whitlatch, 2002), interventions seldom focus on this item (Carretero, Garcés, Ródenas, & Sanjosé, 2009). …”
Section: Safety Of Care Recipientmentioning
confidence: 99%
“…Psycho-educational programs might alleviate the emotional discomfort of informal caregivers associated with social-relational issues, and provide them with skills and strategies to face the challenge of caregiving (Lyons et al, 2002). Such programs may also acknowledge and support informal caregivers in the knowledge that the (former) relationship has changed, and that meaningful joint activities have become impossible; this might stimulate informal caregivers to find new ways to achieve joint activities.…”
Section: Safety Of Care Recipientmentioning
confidence: 99%